Relationship between serum calprotectin (S100A8/9) and clinical, laboratory and ultrasound parameters of disease activity in rheumatoid arthritis: A large cohort study - Hurnakova, Jana; Hulejova, Hana; Zavada, Jakub; Hanova, Petra; Komarc, Martin; Mann, Herman; Klein, Martin; Sleglova, Olga; Olejarova, Marta; Forejtova, Sarka; Ruzickova, Olga; Vencovsky, Jiri; et al. (PloS one, 2017)
BACKGROUND: Calprotectin may be a sensitive biomarker of rheumatoid arthritis (RA) disease activity. OBJECTIVES: In the current study, we investigated whether calprotectin is a better biomarker than CRP for predicting clinical activity and ultrasound parameters in patients with RA. METHODS: A total of 160 patients with RA underwent clinical (swollen joint count-SJC, tender joint count-TJC, Disease Activity Score-DAS28, Clinical Disease Activity Index-CDAI, and simplified Disease Activity Index-SDAI) and ultrasound (German US7) examination. Clinical and laboratory measures were correlated with ultrasound findings using Spearman´s correlation coefficient. Differences in serum calprotectin levels in patients with variable disease activity according to the DAS28-ESR and CDAI scores were assessed using ANOVA. Multivariate regression analysis was used to determine the predictive values of calprotectin, CRP and SJC for CDAI and PD US synovitis scores. RESULTS: Serum calprotectin was significantly associated with DAS28-ESR (r = 0.321, p<0.001), DAS28-CRP (r = 0.346, p<0.001), SDAI (r = 0.305, p<0.001), CDAI (r = 0.279, p<0.001) scores and CRP levels (r = 0.556, p<0.001). Moreover, calprotectin was significantly correlated with GS (r = 0.379, p<0.001) and PD synovitis scores (r = 0.419, p<0.001). The multivariate regression analysis showed that calprotectin is a better predictor of the CDAI score and PD US synovitis than CRP. CONCLUSIONS: The results of this study support an additional role of calprotectin in assessing inflammatory activity in patients with RA.
Keywords: dospělí; Arthritis, Rheumatoid; Female; revmatoidní artritida; C-Reactive Protein; ultrasonografie; Adult; ženské pohlaví; lidé; Ultrasonography; leukocytární L1-antigenní komplex; kohortové studie; Cohort Studies; Male; lidé středního věku; C-reaktivní protein; mužské pohlaví; Leukocyte L1 Antigen Complex; Middle Aged; Humans